UI development and functionality testing automation in android application - Taus, Shehjad Ali; Hasan, Riazul; Rasul, Golam; Tabassum, Anila; Muttakin, Khondoker Al (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.